Long term results of follow-up after HPV self-sampling with devices Qvintip and HerSwab in women non-attending cervical screening programme - Bokan, Teodora (Radiology and oncology (Ljubljana), 2021)
We are presenting the results of the Slovenian human papillomaviruses (HPV) self-sampling pilot study in colposcopy population of National Cervical Cancer Screening Programme ZORA for the first time. One-year and four-year follow-up results are presented for two different self-sampling devices. Participants and methods. A total of 209 women were enrolled in the study at colposcopy clinic. Prior to the gynaecological examination, all women performed self-collected vaginal swab at the clinic; 111 using Qvintip and 98 using HerSwab self-sampling device. After self-sampling, two cervical smears were taken by a clinician; first for conventional cytology and second for HPV test. After that, all women underwent colposcopy and a cervical biopsy if needed. We compared sensitivity, specificity, and predictive values of cytology (at the cut-off atypical squamous cells of undetermined significance or more ASC-US+) and HPV test (on self- and clinician-taken samples) for the detection of cervical intraepithelial neoplasia grade 2 or more (CIN2+) after one and four years of follow-up. Hybrid Capture 2 (HC2) assay was used for all HPV testing. Results. The mean age of 209 women was 37.6 years and HPV positivity rate 67.0% (140/209), 36.9 years and 70.3% (78/111) in the Qvintip group and 38.4 years and 63.3% (62/98) in the HerSwab group, respectively. Overall, percent agreement between self and clinician-taken samples was 81.8% (kappa 0.534) in the Qvintip and 77.1% (kappa 0.456) in the HerSwab group. In the Qvintip group, the longitudinal sensitivity, specificity, positive and negative predictive values were 71.8%, 75.0%, 83.6%, 60.0% for cytology; 83.1%, 51.3%, 75.6% and 62.5% for HPV test of self-taken samples and 94.4%, 57.5%, 79.8% and 85.2% for HPV test on clinician-taken samples. In the HerSwab group, the corresponding results were 71.7%, 46.7%, 61.3%, 58.3% for cytology; 75.0%, 47.7%, 62.9% and 61.8% for HPV test on self-taken samples and 94.3%, 44.4%, 66.7% and 87.0% for clinician-taken samples, respectively. Conclusions. The results confirm that HPV self-sampling is not as accurate as clinician sampling when HC2 is used. All HPV tests showed a higher sensitivity in detecting CIN2+ compared to cytology. Due to non-inferior longitudinal sensitivity of HPV self-sampling compared to cytology, HPV self-sampling might be an option for non-attenders to the National Cancer Screening Programme.
Keywords: citologija; cytology; high-grade intraepithelial lesion; HPV self-sampling; intraepithelialne lezije; presejalni programi; screening programmes; testi HPV